Where Skilled Nursing Facility Residents Get Acute Care: Is the Emergency Department the Medical Home?. (August 2021) - Venkatesh, Arjun K.; Gettel, Cameron J.; Mei, Hao; Chou, Shih-Chuan; Rothenberg, Craig; Liu, Shu-Ling; D'Onofrio, Gail; Lin, ZhenQiu; Krumholz, Harlan M.
Objectives: This study aimed to characterize the distribution of acute care visits among Medicare beneficiaries receiving skilled nursing facility (SNF) services. Methods: We conducted a cross-sectional analysis of a 20% sample of continuously enrolled Medicare beneficiaries in the 2012 Chronic Condition Warehouse data set. Beneficiaries were grouped by the number of days of SNF services, and acute care visits were categorized as "before SNF, " "during SNF, " or "after SNF." Results: Among the 10, 717, 786 Medicare beneficiaries analyzed, 384, 312 (3.6%) had at least one SNF stay. Discussion: Beneficiaries who received SNF services had a higher proportion of acute care visits made to emergency departments (EDs) than beneficiaries who did not receive SNF services. Also, a higher proportion of acute care visits were made to EDs by beneficiaries after a SNF stay in comparison to residents actively residing in a SNF. The acute care capabilities of SNFs and post-SNF transitions of care to the community setting are discussed.